Cantharidic acid induces apoptosis through the p38 MAPK signaling pathway in human hepatocellular carcinoma. Issue 3 (21st November 2017) - Feng, I‐Che; Hsieh, Ming‐Ju; Chen, Pei‐Ni; Hsieh, Yi‐Hsien; Ho, Hsin‐Yu; Yang, Shun‐Fa; Yeh, Chao‐Bin
Abstract: Cantharidin analogs exhibit anticancer activities, including apoptosis. However, the molecular mechanisms underlying the effects of cantharidic acid (CA), a cantharidin analog, on apoptosis in hepatocellular carcinoma (HCC) cells are unclear. Thus, in this study, we evaluated the anticancer activities of CA by investigating its ability to trigger apoptosis in SK‐Hep‐1 cells. Our data demonstrated that CA effectively inhibited the proliferation of SK‐Hep‐1 cells in a dose‐dependent manner. Furthermore, CA effectively triggered cell cycle arrest and induced apoptosis, as determined by flow cytometric analysis. Western blotting revealed that CA significantly activated proapoptotic signaling including caspase‐3, −8, and −9 in SK‐Hep‐1 cells. Moreover, treatment of SK‐Hep‐1 cells with CA induced the activation of ERK, p38, and c‐Jun N‐terminal kinase. Moreover, the inhibition of p38 by specific inhibitors abolished CA‐induced cell apoptosis. In conclusion, our results indicated that CA induces apoptosis in SK‐Hep‐1 cells through a p38‐mediated apoptotic pathway and could be a new HCC therapeutic agent.